Aspectos cognitivos dos manuais de instruções: um estudo de caso em aparelhos de DVD - Torres, Mércil Leite de Oliveira (2006)
This work aims to present an investigation on the level of understanding in the informative texts enclosed in manuals of instructions of a DVD set, trying to identify what makes consumers use or not manuals of instructions which accompany the products. It analyses factors that affect the motivation to use manuals and, linguistically, to verify whether the language used in the manuals is adapted for the understanding of the information by the consumer. Under an ergonomic approach, the research tries to recognize whether it is accordance in the information contained in manuals. According to the production engineering, it is very important to insert the best production practical and administration of the product in the companies, aiming the best competitiveness, The present study suggests a route to evaluate manuals of instructions of a DVD set, using for that a questionnaire with closed questions and an open one, applied to students, employees and teachers of an agricultural school bonded to Rio Grande do Norte Federal University. The results can contribute to provide helps to industry in presentation quality betterment of its information, and becoming the consumer integral part of that improvement process